Four Pseudopoda species (Araneae: Sparassidae) from southern China - Quan, Dan; Zhong, Yang; Liu, Jie (Zootaxa, 2015)
Four species of the genus Pseudopoda are recorded from southern China. Three new species are described: Pseudopoda bicruris sp. nov. (male, female; Hainan Province), Pseudopoda mediana sp. nov. (male, female; Hainan Province), Pseudopoda tiantangensis sp. nov. (male, female; Hubei Province). The female of Pseudopoda lushanensis (Wang, 1990) from Jiangxi Province is described for the first time.